Whole Exome Sequencing, Familial Genomic Triangulation, and Systems Biology Converge to Identify a Novel Nonsense Mutation in TAB2‐encoded TGF‐beta Activated Kinase 1 in a Child with Polyvalvular Syndrome. (25th July 2016) - Ackerman, Jaeger P.; Smestad, John A.; Tester, David J.; Qureshi, Muhammad Y.; Crabb, Beau A.; Mendelsohn, Nancy J.; Ackerman, Michael J.
ABSTRACT: Objective: To use whole exome sequencing (WES) of a family trio to identify a genetic cause for polyvalvular syndrome. Methods and Results: A male child was born with mild pulmonary valve stenosis and mild aortic root dilatation, and an atrial septal defect, ventricular septal defect, and patent ductus arteriosus that were closed surgically. Subsequently, the phenotype of polyvalvular syndrome with involvement of both semilunar and both atrioventricular valves emerged. His family history was negative for congenital heart disease. Because of hypotonia, myopia, soft pale skin, joint hypermobility, and mild facial dysmorphism, either Noonan syndrome‐ or William syndrome‐spectrum disorders were suspected clinically. However, chromosomal analysis was normal and commercially available Noonan syndrome and William syndrome genetic tests were negative. Whole exome sequencing of the patient and both parents was performed. Variants were analyzed by sporadic and autosomal recessive inheritance models. A sporadic mutation, annotated as c.1491 T > A, in TAB2, resulting in a nonsense mutation, p.Y497X, in the TAB2 ‐encoded TGF‐beta activated kinase 1 (TAK1) was identified as the most likely disease‐susceptibility gene. This mutation results in elimination of the terminal 197 amino acids, including the C‐terminal binding motif critical for interactions with TRAF6 and TAK1. Conclusions: The combination of WES, genomic triangulation, and systems biology has uncovered perturbations in TGF‐beta activated kinase 1 signaling as a novel pathogenic substrate for polyvalvular syndrome.